2018
DOI: 10.1111/pbr.12642
|View full text |Cite
|
Sign up to set email alerts
|

White lupin (Lupinus albus) variation for adaptation to severe drought stress

Abstract: This study aimed to reduce the gap of knowledge on white lupin drought tolerance variation, by assessing the grain yield of 21 landraces from major historical cropping regions, one variety and two breeding lines in a large phenotyping platform that imposed controlled severely stressed or moisture‐favourable conditions after an initial stage of favourable growth. Drought stress reduced grain yield by 79%. Genetic correlation coefficients indicated moderate consistency of genotype responses across conditions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Affected regulatory pathways include, among others, the flowering time control (Nelson et al, 2010). The rapid flowering of domesticated germplasm may favor drought escape and adaptation for spring sowing in higher latitudes (Annicchiarico et al, 2010(Annicchiarico et al, , 2018Berger et al, 2017). However, the observed extension of the vegetation period has raised the demand for germplasm with intermediate phenology and cross-environment adaptation.…”
Section: Pal Allele Carrying Intermediate Phenology and Light Vernalimentioning
confidence: 99%
“…Affected regulatory pathways include, among others, the flowering time control (Nelson et al, 2010). The rapid flowering of domesticated germplasm may favor drought escape and adaptation for spring sowing in higher latitudes (Annicchiarico et al, 2010(Annicchiarico et al, , 2018Berger et al, 2017). However, the observed extension of the vegetation period has raised the demand for germplasm with intermediate phenology and cross-environment adaptation.…”
Section: Pal Allele Carrying Intermediate Phenology and Light Vernalimentioning
confidence: 99%
“…Introduction of preferred alleles on one-by-one basis can be inefficient, due to epistatic interactions between major components of flowering regulatory network [ 90 ]. Phenotyping studies revealed that white lupin germplasm collection has variability of many agronomic traits, including, besides time to flowering, winter survival, pod fertility, pod wall proportion, number of leaves on the main stem, several yield related traits and anthracnose resistance [ 11 , 12 , 13 , 29 , 91 , 92 , 93 , 94 ]. Despite relatively small genotype sample size (83 landraces and eight varieties), genomic prediction for grain yield, winter plant survival and onset of flowering provided prospective output, manifested by model-based predictive ability values as high as 0.84–0.86 [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, wide use of lupins for human consumption was hampered by their bitter taste caused by a high alkaloid content, but this issue has been fixed in modern cultivars [ 9 ]. Considering the agronomic characteristics of white lupin, there is still high potential for further yield increases and drought tolerance improvement by exploitation of existing germplasm resources [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern breeding programs mainly focus on yield stabilization, resistance to abiotic stresses, biochemical structure associated with seed quality, resistance to diseases (mainly to anthracnose) and late maturing [ 30 , 77 , 78 ].…”
Section: Breeding Of Lupinsmentioning
confidence: 99%
“…The main research work has been focused on identification of genetic material that can be utilized in breeding programs. In Italy 21 landraces, one commercial variety and two breeding lines were screened under severe drought stress and favourable conditions through a phenotyping platform that revealed substantial variation in white lupin available genetic material [ 134 ]. Two yellow lupin ( L. luteus ) cultivars were tested under drought conditions in order to examine how manipulation of polyamine biosynthesis by using inhibitors of their biosynthesis can influence lupin drought tolerance but the results are not straightforward [ 135 ].…”
Section: Breeding Of Lupinsmentioning
confidence: 99%